Estudios del territorio: potencialidad socio-espacial para los procesos de desarrollo (2011)
ABSTRACT: Today, based on the postulates of geography, specifically the critical geography (Harvey, 2003, 2007; Santos, 1996, 1997, 2000), the scientific and academic interest in the subject of the territory, specially by his study, returns. This requires, therefore, to recreate and develop notions of territory that are accurated, appropriated and relevant to current societal context, and anyway, what you need when it comes to their studies it is, because this constitutes a socio-spatial capability to understand contemporary to them, exploit it to them, to appropriate it and use it as support for social, economic, political, environmental and territorial and, among others, of communication, linked with the reality and will change their orientation to development scenarios, improves conditions and the quality of life together. In this regard, the study of the territory emerges as ascientific problem of contemporary interest.